Estudo do processo de produção de fator de proteção solar (FPS) mineral: etapas, legislação e lançamento no mercado - Mendes, Letícia Carolina (Universidade Federal de São Carlos, 2024)
Exposure to the sun is beneficial to the health of human beings as long as the necessary precautions are taken, such as correct photoprotection, since unlight induces the production of D vitamin. Despite this, ultraviolet radiation can cause damage to DNA, chemical changes and histological in epidermal cells, immunosuppression, cataracts, premature aging, and other diseases. Photoprotection is an essential tool that prevents these and other harmful effects on health. For this reason, the population's awareness of the risks arising from exposure to the sun is growing and, following this trend, the market is offering its answers. With the aim of offering better products that meet the population's demand, offering affordable prices and quality, the segment requires improvement of formulations and improvement in the quality of raw materials, which in turn, impact the development of more efficient production processes and, consequently, the need for investment in R&D. Therefore, the objective of the work is to evaluate the stages of production of mineral sunscreen in a medium-sized company that serves the master sector, as well as the marketing aspects and legislation involved in launching the product on the market. The production of mineral sunscreens is therefore a complex process that involves several steps, from the choice of ingredients to the final packaging of the product. Companies that want to stand out in this market need to be aware of consumer demands, sanitary regulations, and technological innovations. Thus, companies can guarantee the quality of their products, increase their competitiveness, and achieve success in this promising market.
Study of the sun protection factor production process mineral: stages, legislation and market launch
Keywords: FPS mineral; processo produtivo; ENGENHARIAS::ENGENHARIA QUIMICA::PROCESSOS INDUSTRIAIS DE ENGENHARIA QUIMICA